Introduction to executive protection - June, Dale L. (CRC Press, Taylor & Francis Group, 2016)
At a time when personal security risks are on the rise internationally, Introduction to Executive Protection, Third Edition takes readers beyond "the wizard's curtain" of fear, unawareness, and surprise to give them the tools to sharpen or renew their skills so those they are tasked with protecting remain safe.